〈Original Papers〉アコヤ(真珠)貝アルファチューブリン遺伝子の単離およびその特徴 - Miyashital, Tomoyuki; ミヤシタ, トモユキ; Takami, Akiko; タカミ, アキコ; Sugimoto, Yui; スギモト, ユイ; Sakai, Ayumi; サカイ, アユミ; Takagi, Ryosuke; タカギ, リョウスケ (近畿大学生物理工学部, 2013)
[要旨] 真珠貝であるアコヤ貝アルファチューブリン遺伝子を単離した。この遺伝子の長さは1678bpで、451個のアミノ酸から構成される大きさ42kDaのタンパク質をコードしており、アルファチューブリン2と命名した。アミノ酸配列中には、α-/β-チューブリンの重合に必要なグアノシン3リン酸が結合する部位が存在する。さらに、翻訳後修飾部位として、リン酸化を受ける79番目と336番目の残基であるアルギニンとリジンが、また、アセチル化を受ける40番目の残基であるリジンが存在する。近隣結合法(NJ法)による系統樹は二枚貝であるアコヤ貝より単離したこのアルファチューブリンは二枚貝より巻貝のアルファチューブリンに近いことを示した。RT-PCR法でmRNAの発現部位を解析した結果、外套膜緑、貝柱、鰓および肝臓で発現が観察されたが、足と外套縁膜では発現していなかった。これら二つの組織ではファミリーの他のアルファチューブリン遺伝子が発現していると考えられる。 [Abstract] We have isolated a full-length Pinctada fucata a-tubulin gene that is one of the genes obtained in the process of selecting the BMP (Bone Morphogenetic Protein) type II receptor gene. The 1678 base pair (bp) length of a-tubulin cDNA encodes 451 amino acids and the calculated mass is 42 kDa. The gene belongs to one of the Pinctada fucata a-tubulin family and was designated a-tubulin 2. The amino acid sequence of Pinctada fucata a-tubulin 2 contains the GGGTGSG domain that is a Guanosine triphosphate (GTP) nucleotide-binding site required for a-/I3-tubulin polymerization, and also contains putative posttranslational modification sites that are the phosphorylation residues at arginine (R) 79 and lysine (K) 336, and an acetylation residue at lysine (K) 40. Phylogenetic analysis revealed that bivalvia Pinctada fucata a-tubulin 2 is closer to a gastropoda (Ilyanassa obsoleta, Patella vulgata) a-tubulin than that of a bivalvia (Scrobicularia plana, Crassostrea gigas, Mytilus galloprovincialis). RT-PCR analysis showed that a-tubulin 2 messenger RNA was expressed in mantle edge, gill, adductor muscle and liver but not in mantle pallial or foot. It is expected that other members of the a-tubulin family are expressed in mantle pallial and foot. This study was supported by the Project Research of the school of Biology Oriented Science and Technology No. 09-IV-21, 2010. application/pdf departmental bulletin paper